Risk and Protective Factors of Self-Harm and Suicide in Adolescents in The Era of Society 5.0: A Systematic Review - Trihaningsih Puji Astuti; Nurul Hidayati; Fauzi Tsanifiandi; Rr Dian Tristiana (Fundamental and Management Nursing Journal, 2024)
Introduction: Suicide and self-harm have been ranked as the fourth leading causes of mortality among adolescent population. Preventive interventions are necessary due to the rising prevalence. The aimed of this study was to identify the risk and protective factors of self-harm and suicidal behavior among adolescents in the era of society 5.0. Methods: This study was a literature review. Published, English articled were retrieved from Scopus, Web of Science, PubMed, and CINAHL databases, limited to the last five years from 2018 to 2023. The specific keywords used to search for articles were ("Self-harm" OR "Self-injurious behavior" OR "Self-destructive behavior") AND suicid* AND (adolescent OR youth OR teenager). Results: Eleven (n=11) articles were synthesized and resulted based on thematic analysis of eleven articles, five risk factors and three protective factors for self-harm and suicidal behavior in adolescents were found. Five risk factors consist of family dysfunction, experience of being a victim of bullying, history of self-harm, maladaptive coping and having a history of mental disorders. Meanwhile, three protective factors for prevention are family support and attachment, school support and positive activities. Conclusions: The rapid influence of technology in the era of society 5.0 which was triggering self-harm and suicide behaviors can be suppressed with a strong support system in adolescents. Family, education, and peers play crucial roles in fostering adolescents' emotional well-being. Considering both risk and protective factors, Further examination is to deeply understand adolescents engage in self-harm and suicide is warranty.